2008
DOI: 10.1590/s0100-736x2008000900002
|View full text |Cite
|
Sign up to set email alerts
|

Morfofisiologia da inervação do diafragma de ovinos

Abstract: Thirty diaphragms of sheep of Santa Inês breed were studied regarding their origin, division and arrangement of the right and left phrenic nerves (Fde), and the participation of other nerves in the innervation of the diaphragm. By fixing and dissecting pieces, it was found that phrenic nerves (F) frequently come from the ventral branches of the 5 th (C5) and 6 th (C6) cervical spinal nerves (Ec), at right (46.67%) and at left (43.33%). The F often form a lumbocostal trunk, sternal branches at right (40.00%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
(9 reference statements)
1
8
1
1
Order By: Relevance
“…Combined contribution of the ventral branches of C5 and C6 was found in 48 specimens (88.88%), differing from the results found by Getty (1981) [3] for swine and ruminants, and by Dyce, Sack, and Wensing (2010) [11] for domestic ruminants, who reported that this nerve originates from the ventral branches of C5, C6, and C7; this configuration was found in three (5.55%) animals in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…Combined contribution of the ventral branches of C5 and C6 was found in 48 specimens (88.88%), differing from the results found by Getty (1981) [3] for swine and ruminants, and by Dyce, Sack, and Wensing (2010) [11] for domestic ruminants, who reported that this nerve originates from the ventral branches of C5, C6, and C7; this configuration was found in three (5.55%) animals in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…[6][7][8][9][10][11][12][13] On the other hand, our findings are in agreement with other studies that pointed out the contribution of the intercostal nerves to the innervation of the diaphragm. 4,5,[14][15][16][17][18][19] We observed the innervation of the diaphragm by the intercostal nerves 6 to 12, mainly by the 8 th nerve. Rosenblueth et al (1961), 4 even if they observed the participation of the intercostal nerves 4 to 10, observed that the major intercostal nerve acting in the innervation of the diaphragm was the 8 th nerve.…”
Section: Discussionmentioning
confidence: 99%
“…It is also crucial to assist the abdominal muscles during vomiting, coughing, urination, sneezing, defecation, and labor. 4 Almeida et al (2008) 5 describe the intercostal nerves, mainly those from the 7th to the 9 th , as primary efferent pathways for some of these actions or reflexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em relação a origem e ramificação do nervo frênico em fetos de suínos da linhagem Pen Ar Lan, observou-se que a contribuição para a formação desse nervo ocorreu principalmente pelo ramos ventrais do quinto nervo espinhal cervical (C5) e sexto nervo espinal cervical (C6), sendo que ramos ventrais do sexto nervo espinhal cervical (C6) foi encontrado em todos os animais analisados. Corraborando com Almeida et al (2008) (MIGLINO et al, 1985), não sendo referido sobre a predominância da trifurcação.…”
Section: Discussionunclassified